Digital Talent: Designing Recruitment and Employee Development Strategies to Face Corporate Digital Transformation - Sayugo Adi Purwanto; Siti Munawaroh; Dwibin Kannapadang (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Digital transformation has become a key agenda for organizations facing technological disruption and dynamic market demands. However, organizational readiness for transformation is highly influenced by human resource management strategies, particularly in recruiting and developing digital talent. This study aims to analyze the impact of digital recruitment strategies and digital talent development on organizational readiness for digital transformation, and to examine the mediating roles of organizational trust and employee engagement. This research adopts a quantitative approach using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The sample consists of 150 respondents working in service and manufacturing organizations undergoing digital transformation. The findings reveal that both digital recruitment and digital talent development strategies have a positive and significant influence on organizational readiness. Moreover, organizational trust and employee engagement partially mediate the relationship between digital HR strategies and organizational readiness. These results support the resource-based view and dynamic capabilities theory, highlighting the strategic role of human capital in driving successful digital transformation. Practical implications suggest that organizations should integrate digital strategies into HR management to sustainably foster trust and engagement among employees. This study recommends policy innovations in digital HRM to enhance organizational readiness in the era of transformation.